Augustins vurdering af Rom og romerne - Larsen, Bent Dalsgaard (Religionsvidenskabeligt Tidsskrift, 1991)
Saint Augustine's judgement of Rome and the Romans operates on different levels. He criticizes comtemporary society, e.g., for its education and its ludi scaenici, and he refers to Christianity as leaven in society (epist. 138) and to the christian community of Acts 4, 31-35 as a model (the Rule). But his main censure is directed against Republican Rome as concept of Rome because of its libido dominandi, its aviditas gloriae and its false cult and political religion. The ancient Rome was, on grounds of principle, not able to furnish the moral basis necessary to every society. This problem Augustine consideres in the more general and comprehensive theological perspective of the two ciuitates: any effort to build a society on human forces alone (secundum hominem) is futile and will result in an anti-society, whereas a life according to God's will (secundum Deum) - and this alone - is truly social. But ontologically speaking, the evils of Rome and the Romans were not substantial, but evils of the will, and the ordo naturalis has not been totally destroyed. However, it is only by God's grace in christ that man van be restored, and justice and peace in society and between nations must have its sosurce in the justice and peace of God according to the order of Matthew 6,33.